Milky secretion after late breast reconstruction with latissimus dorsi musculocutaneous flap with implant - Gabriel de Almeida Arruda Felix; Ariane Garcia; Joel Veiga; Lydia Masako Ferreira; Daniela Francescato Veiga (Revista Brasileira de Cirurgia Plástica)
We present a rare case of a 28-year-old patient with invasive ductal carcinoma who underwent neoadjuvant chemotherapy, modified radical mastectomy, radiotherapy, and late breast reconstruction with latissimus dorsi flap associated with the implant. One year later, she underwent reconstruction of the nipple-areola complex over the cutaneous island of the latissimus dorsi flap with a total skin graft from the thigh and graft from the caudal portion of the contralateral papilla. She became pregnant six months after the reconstruction of the nipple-areola complex and, unexpectedly, presented milk production by the reconstructed breast.